DEVELOPING ACTIVITIES, INDEPENDENCE AND ASPECTS OF MOTORIK HALUS USING THE EXTREAM MODEL IN GROUP B2 CHILDREN - hairunnisa hairunnisa; Celia Cinantya (E-CHIEF Journal, 2022)
AbstractThis studyaims to describe teacher activities and analyze activities, independence and fine motor aspects of children.  The problem in this i researchis the low activity, independence and motor aspects ofchildren. This is due to  the lack of meaningful learning, children lack opportunities in independent learning activities, and lack of activities that train children's fine motor skills.  An attempt to solve this problem is to use the EXTREAM model (E Xplicit insTRuction, kolasE and mediA alaM materials).  This  research approach uses a qualitative approach with a type of classroom action research (PTK), the subject of research in group B2 children in Aisyiyah Bustanul Athfal 15 Banjarma sin Kindergarten. Data collection techniques use observation sheets on teacher activities, children's activities, independence and fine motor aspects. Meanwhile, data analysis is the analysis of descriptions  and cross tables and  achievements and criteria.  The results showed that teacher activity achieved very good criteria at meeting  3. The child's activity at meeting 3 reaches the criteria of "All Active Students". Thechildren at meeting 3 achieved  the criteria of "All Independent Students". In addition, the results of the child's fine motor development at the last meeting reached 100% of children who succeeded by obtaining (BSH) and (BSB).  It was concluded that the EXTREAM model can improve the activity, independence and results of fine motor development of the child very well. It is recommended to use the EXTREAM model as a reference for effective learning of teachers to realize the results of the development of fine motor aspects better.Keywords: Activity, Independence, Fine Motor, Explicit Instruction, Natural Material Media.